Pharmacocorrection of mitochondrial dysfunction and energy imbalance of substantia nigra neurons in experimental Parkinson's disease in rats - Maramukha, Volodymyr (Journal of Education, Health and Sport, 2020)
Parkinson's disease (PD) is a progressive disease and the incidence increases markedly with age, treatment has significantly improved the quality of life of patients with PD, but statistics show that these patients continue to show shorter life expectancies compared to the general population. Aim of the study. To investigate the features of changes in energy balance and mitochondrial dysfunction on the basis of experimental studies in rats in the modeling of PD and justify the development of possible treatment regimens with specific neuroprotective effects on the dopaminergic system. Materials and methods. The study was carried out on 90 Wistar rats at the age of 6 months weighing 220-290 grams. Parkinsonism was induced by the administration of the neurotoxin MPTP (N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) to experimental rats with neuroprotective treatment: I – Intact (passive control); II – animals with experimental Parkinson's disease (PD, active control); III – PD + Amantadine (AM) IV – PD + AM + Cerebrocurin; V – PD + AM + Pramistar; VI – PD + AM + Gliatilin; VII – PD + AM + Noofen; VIII – PD + AM + Pronoran; IX – PD + AM + Melatonin. Results. Under conditions of formation of experimental PD in rats develops energy deficiency of neuronal cells and dysfunction of the Krebs cycle with a predominance of anaerobic oxidation of the substrate, as well as the development of mitochondrial dysfunction. Prescribed neuroprotective drugs significantly improved energy metabolism in the brain of rats with PD within statistical significance, increased levels of ATP and ADP, enzymatic activity of mCPK and ATPase, decreased levels of AMP, especially pronounced drugs melatonin, cerebrocurin, gliatilin and pronoran. Neuroprotective therapy of experimental PD in rats contributed to a statistically significant increase in the values of pyruvate, malate, LDH and MDG, and also led to a decrease in the values of lactate and lactic acidosis in brain tissues. The appointment of neuroprotective therapy with basic amantadine therapy led to an increase in energy charge, energy potential, phosphorylation index and thermodynamic control of respiration in the mitochondria of neurons, especially in the groups of melatonin, cerebrocurin, gliatilin and pronoran. Conclusions. Pharmacocorrection of mitochondrial dysfunction and energy imbalance of dopaminergic neurons in experimental PD in rats may indirectly or directly inhibite to the progression of pathology in PD.